Effect of low-molecular-weight heparins on anti-Xa peak levels and adverse reactions in Chinese patients with recurrent spontaneous abortion: a single-center, observational study - Wenxin Bai; Xinyang Zhang; Si Sun; Qiaohong Wang; Congcong Li; Xiaoxin Zhang; Aimin Zhao (BMC, 2021)
Abstract Objective To compare three commonly used low-molecular-weight heparins (LWMHs) in the treatment of recurrent spontaneous abortion (RSA) by evaluating the anti-Xa peak levels and adverse reactions. Methods In this single-center, observational study, we enrolled 310 patients with RSA in whom anti-Xa levels were measured during pregnancy. Patients were divided into three groups according to the LMWH they used: the nadroparin group, enoxaparin group and dalteparin group. We compared the peak anti-Xa levels and the coagulation status of each group, and analyzed the incidence of adverse reactions, including local allergy, liver and renal dysfunction, and the impact on platelet. Results Patients in the enoxaparin group had a higher anti-Xa peak level than those in the nadroparin group (0.80 ± 0.22 IU/ml vs. 0.61 ± 0.24 IU/ml; P <  0.0001), although most patients in the three groups reached the target concentration of anti-Xa. Furthermore, patients in the enoxaparin group had a more stable anti-Xa levels during pregnancy. In addition, patients in the nadroparin group had a higher rate of local allergy than those in the enoxaparin group (60.5% vs. 42.5%; P = 0.004) and those in the dalteparin group (60.5% vs. 33.3%; P = 0.002). Further examination by the type of local allergy indicated a dramatic difference in pruritus and induration between the nadroparin group and the other two groups. No difference was found in the incidence of liver and renal dysfunction and thrombocytopenia. Conclusion Compared with nadroparin and daltepatin, enoxaparin showed a better performance regarding anti-Xa levels and the incidence of adverse reactions in the treatment of RSA.